Pengembangan Ranah Afektif Kimia melalui Penyuluhan kepada Masyarakat - Familia Novita Simanjuntak (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2018)
Socializations are generally conducted to improve the societies’ knowledge, learning skill simultaneously with character building and empowerment by illuminating the topics which are relevant to their needs (Ibrahim, Thomas and Fine, 2003; van den Ban and Hawkins, 1999). Mardikanto (1987) stated that socialization can increase the society’s participation on development, especially on chemistry awareness community development. Chemistry is a branch of science which studies about composition, structure, properties and change of matter. Chemistry is generally known as abstract science so that result the chemo-phobia and cause lower chemistry learning interest, especially on students (Leong Suk Yee and Lay Yoon, 2014). This research studies about the advantages of chemistry socialization toward the society in developing affective chemistry domain on students and community. This research quantitatively analyzes 159 data which are purposive randomly gathered from 159 participants (junior and high school students, youth organization, and students of equivalency school). The results show that socialization toward the society develops chemistry affective domain on students reaches 40% - 71% by classifying the relevant examples from daily life, explaining the topic and good responding in discussion, motivating the society and developing the arguments as the conclusion. The achievement of chemistry affective domain on society reaches 75% by accepting the topics of socialization in a good manner, following the suggestions and directions during the socialization, arranging some questions about the topic and interesting on advantages of socialization. The socialization toward the society can be the alternative of learning method to develop the chemistry affective domain. Keywords: education; chemistry affective domain; chemophobia.